Out of school : information art and the Toronto School of Communication - Lauder, Adam, 1981- (McGill-Queen's/Beaverbrook Canadian Foundation studies in art history., 2022)
"Through a series of focused and interconnected case studies, Out of School explores the long history of information art associated with the Toronto School of Communication. It highlights the perspectives of artists inspired by the speculations of Marshall McLuhan and colleagues as well as the philosophical underpinnings of the Toronto School's ideas about information. Using pre-Internet media such as telex and the telecopier, the artists explored in this book materialized visionary concepts of information without the aid of computers. Harbingers of contemporary digital culture, Bertram Brooker, N.E. Thing Co., Robert Smithson, Wyndham Lewis, General Idea, and other artists approached information as something embodied, sensorial, and social. Art historian Adam Lauder recontextualizes this qualitative philosophy of information in relation to quantitative discourses and methodologies, which these creative figures make visible--sometimes inadvertently or satirically--through artworks that operate at the interface between art and business. While exploring how utopian information ontologies struggled to account for markers of identity and difference, including Indigeneity, gender, and sexual diversity, this book also highlights instances when information art was able to carve out spaces of agency and resistance. Offering an essential reassessment of the legacies of the Toronto School of Communication, Out of School broadens the network of practitioners connected to the School to include visual artists active both within and beyond Canada. In doing so, it proposes that artists made significant contributions to theory in their own right."--